SUBJECT POSITION AS A BASIS HUMANITIES EDUCATION - Hrybenko, H.Ye. (Pedagogy of Higher and Secondary Education, 2008)
The article is dedicated to question of the subjective professional-personal position of the future specialist to conditions of the personal education.